(untitled) (CAHIERS MAGELLANES-NS, 2024)
The study examines the social legal and economic exclusion of sex workers of Banchhada community which is a tribe in central India that is traditionally identified with prostitution. Mandsaur districts of Madhya Pradesh, India has social sanction for work related to prostitution. Sex work in India has existed even before many ideologies that thrive in recent times, earlier people and civilisation use to rely on this as form of business. Today, in India many things have been reformed and many things have been abolished for the sake of the welfare of the country and society. In India, today prostitution is something people degrade, bad mouth, compares it to violence. People also believe sex work as taboo and exclude it from the society. This paper examines the contrast in the living of the Banchhada community with rest of the society. Few members of the community were directly asked set of questions related to their social, and economic status. and accordingly, conclusions were drawn. The authors also attempts to explain the wretched condition of women who are being forced to work as a sex worker.